2019
DOI: 10.2147/opth.s199771
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safety of anti-VEGF treatments in a diabetic rat model and retinal cell culture</p>

Abstract: Purpose To analyze the safety of different concentrations of anti-VEGF on retinal cells. Methods Non-diabetic and streptozotocin (STZ)-induced diabetic rats received intravitreal rat anti-VEGF injections that had final vitreous concentrations of 0, 0.0625, 0.125 (clinical dose), and 0.25 mg/mL. Rats were also injected with the clinical dose of ranibizumab. TUNEL assay was performed on sectioned eyes to evaluate apoptotic cells. In vitro, rat retinal cell cultures were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…VEGF is the primary mediator of abnormal diabetic glomerular angiogenesis. Although the beneficial effects of anti-VEGF antibodies have been confirmed in diabetic animal experiments, recent basic and clinical evidence has suggested that blocking VEGF signaling can lead to proteinuria and renal thrombotic microangiopathy ( 17 ), indicating the importance of the normal levels of VEGF in the kidney. Therefore, anti-angiogenic treatment of DN should eliminate the excessive angiogenic response of the glomeruli without accelerating endothelial damage.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF is the primary mediator of abnormal diabetic glomerular angiogenesis. Although the beneficial effects of anti-VEGF antibodies have been confirmed in diabetic animal experiments, recent basic and clinical evidence has suggested that blocking VEGF signaling can lead to proteinuria and renal thrombotic microangiopathy ( 17 ), indicating the importance of the normal levels of VEGF in the kidney. Therefore, anti-angiogenic treatment of DN should eliminate the excessive angiogenic response of the glomeruli without accelerating endothelial damage.…”
Section: Introductionmentioning
confidence: 99%